A Satellite dsRNA Attenuates the Induction of Helper Virus-Mediated Symptoms in Aspergillus flavus - Jiang, Yinhui; Yang, Bi; Liu, Xiang; Tian, Xun; Wang, Qinrong; Wang, Bi; Zhang, Qifang; Yu, Wenfeng; Qi, Xiaolan; Jiang, Yanping; Hsiang, Tom (Frontiers in Microbiology, 2022)
Aspergillus flavus is an important fungal pathogen of animals and plants. Previously, we reported a novel partitivirus, Aspergillus flavus partitivirus 1 (AfPV1), infecting A. flavus. In this study, we obtained a small double-stranded (ds) RNA segment (734 bp), which is a satellite RNA of the helper virus, AfPV1. The presence of AfPV1 altered the colony morphology, decreased the number of conidiophores, created significantly larger vacuoles, and caused more sensitivity to osmotic, oxidative, and UV stresses in A. flavus, but the small RNA segment could attenuate the above symptoms caused by the helper virus AfPV1 in A. flavus. Moreover, AfPV1 infection reduced the pathogenicity of A. flavus in corn (Zea mays), honeycomb moth (Galleria mellonella), mice (Mus musculus), and the adhesion of conidia to host epithelial cells, and increased conidial death by macrophages. However, the small RNA segment could also attenuate the above symptoms caused by the helper virus AfPV1 in A. flavus, perhaps by reducing the genomic accumulation of the helper virus AfPV1 in A. flavus. We used this model to investigate transcriptional genes regulated by AfPV1 and the small RNA segment in A. flavus, and their role in generating different phenotypes. We found that the pathways of the genes regulated by AfPV1 in its host were similar to those of retroviral viruses. Therefore, some pathways may be of benefit to non-retroviral viral integration or endogenization into the genomes of its host. Moreover, some potential antiviral substances were also found in A. flavus using this system.